Actuators of the Seismic Vibrations Sources; Mechanical Engineering, Automation and Control Systems (MEACS) - Moyzes [Moises] B. B. Boris Borisovich; Xiaoliang Zhang; Gavrilin A. N. Aleksei Nikolaevich; Melkov K. V.; Fayngerts A. V. (2015, 2015)
Title screen